Understanding of Comparison Degree Through Jigsaw Cooperative Learning Model: A Brief Report of Qualitative Research - Astutik, Yuli; Albarika, Ayu Grahita; Wibisono, Farah Nabila; Teluma, Katarina Sarabiti (Universitas Muhammadiyah Sidoarjo, 2024)
The purpose of this research is to analyse the steps of teacher in using jigsaw cooperative learning model in increasing students understanding of comparison degree material. This research was conducted using qualitative method through observation of classroom learning activities in one of Muhammadiyah high schools in Sidoarjo. The participants in this study were one English teacher and 17 students of class X-5. The data collected was then analyzed descriptively to find out the behavior and activities of students in the classroom, as well as to analyze the effective learning steps taken by the teacher to help students learn English, Especially on comparison degree material. The jigsaw type cooperative learning model can effectively improve students ability to understand comparison degree material in English learning. This mode not only improves students understanding of the material, but also develops their social and communication skills. Thus, the use of jigsaw model can be considered as one of the effective learning strategies in English teaching.